Management of psychological distress in cancer patients / Ng Chong Guan - Ng, Chong Guan (2017)
Psychological distress is highly prevalent in cancer patients, yet there is a lack of a brief and effective non-pharmacological intervention to address this distress. The current study involved a series of research projects. It started with a retrospective cohort study using a hospital pharmacy database to examine the psychotropic prescription rates among the cancer patients. A meta-analysis and a systematic review on the efficacy of different types of psychotherapy in cancer patient were also carried out. It was followed by a 1-year prospective study examining the association between perceived distress and factors such as anxiety, depression, perceived social support and quality of life among a cohort of breast cancer patients. Subsequently, a cross-sectional study was conducted to investigate the correlation between religiosity, religious coping with anxiety and depression in cancer patients. For the management of distress in cancer patient, a brief 5-minute mindful breathing therapy was developed. A randomized controlled trial (RCT) was conducted to examine the efficacy of this 5-minute mindful breathing. The results showed that psychotropic prescription was higher in cancer patient than in cardiology patients. The 1-year prospective study demonstrated that perceived distress was associated more with anxiety rather than depression. They were negatively correlated with perceived social support and quality of life. The evidence of meta-analysis indicated that the efficacy of psychotherapy in cancer patients was unsatisfactory where only adjunct psychological therapy (APT) showed short-term improvement in anxiety. The result of the RCT showed that 5-minute mindful breathing was a quick, easy to administer and effective therapy for rapid reduction of distress in palliative setting. The long term efficacy of the brief 5-minute mindful breathing in cancer patients needs to be established in the future studies.